2004
DOI: 10.1111/j.1751-0813.2004.tb13248.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the role of antibodies toActinobacillus pleuropneumoniaeserovar 1 and 15 in the protection provided by sub‐unit and live streptomycin‐dependent pleuropneumonia vaccines

Abstract: Objective To evaluate the serological response of pigs receiving either the Porcilis APP vaccine or a modified live vaccine based on a streptomycin‐dependent (SD) strain of Actinobacillus pleuropneumoniae, and then challenged with an Australian isolate of A pleuropneumoniae of either serovar 1 or 15 as a means of understanding the protection provided by both vaccines against serovar 1 but not against serovar 15. Design The serological tests evaluated were serovarspecific polysaccharide ELISA tests (for serova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Since each of the Apx exotoxins confers only partial protection against porcine pleuropneumonia and the distribution of Apx exotoxins varies among the different serotypes, the current commercial vaccine (Porcilis APP, Intervet, Holland) is composed of three toxoids-ApxI, ApxII, and ApxIII-and one 42-kDa outer membrane protein. This subunit vaccine is effective at preventing acute disease, but it neither protects effectively against colonization nor confers cross-serotype protection (8).…”
mentioning
confidence: 99%
“…Since each of the Apx exotoxins confers only partial protection against porcine pleuropneumonia and the distribution of Apx exotoxins varies among the different serotypes, the current commercial vaccine (Porcilis APP, Intervet, Holland) is composed of three toxoids-ApxI, ApxII, and ApxIII-and one 42-kDa outer membrane protein. This subunit vaccine is effective at preventing acute disease, but it neither protects effectively against colonization nor confers cross-serotype protection (8).…”
mentioning
confidence: 99%
“…These vaccines do not effectively prevent colonization and are not widely cross protective (Tumamao et al 2004). As other pathogenic bacteria of multiple serotypes, a major point in the prevention of APP infections is to identify conserved antigens or proteins involved in immunogenicity, which may provide cross-protection against distinct APP serotype infections (Chen et al 2012;Haesebrouck et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been carried out to identify vaccine candidates for efficient cross-protection, such as killed bacterin vaccines and subunit vaccines (Blackall et al 2002;Haesebrouck et al 2004;Zhou et al 2013). These vaccine candidates do not prevent colonization and are not widely cross-protective (Tumamao et al 2004). Therefore, further efforts need to be made for development of more efficient vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, commercially available toxin‐type vaccines have been shown to confer strong protection against a wide variety of A. pleuropneumoniae serovars. However, a recent trial with one of these vaccines, composed of ApxI, ApxII, ApxIII and a 42 kDa outer membrane protein, showed that the vaccine failed to protect swine against challenge with strain HS143 (serovar 15) . The failure of this toxin‐type vaccine may be attributable to differences between the ApxII and ApxIII toxins and specific polysaccharide of serovar 15 and those incorporated in the vaccines .…”
mentioning
confidence: 99%